2018
DOI: 10.1002/smll.201703707
|View full text |Cite
|
Sign up to set email alerts
|

Facile Ionic Liquid‐Assisted Strategy for Direct Precipitation of Eu2+‐Activated Nanophosphors under Ambient Conditions

Abstract: This work describes a novel ionic liquid (IL)-assisted synthesis strategy for a direct and easy production of Eu -doped nanoparticles (NPs), where ILs are also used as fluoride sources to avoid the use of elemental fluorine or toxic hydrofluoric acid. Up to now, the direct synthesis of Eu -doped nanophosphors consisted of an enormous challenge, due to the oxidation to Eu observed in hydrous solution, which is commonly used for the preparation of NPs, generating lattice defects and undesired particle growth or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
0
15
0
4
Order By: Relevance
“…[35][36][37] The ionic liquids (IL) used as (co)solvent are also able to play the key role of surfactants and/or structure directing agents allowing us to tailor the size, the shape and the agglomeration/porosity of the synthesized inorganic nanomaterials and hybrid nanomaterials. [38][39][40][41][42][43][44] In fact, ILs can form extended hydrogen-bond systems in the liquid state to be highly structured, which can serve as the "entropic driver" for spontaneous, well-dened, and extended ordering of nanoscale structures. Thus, synthesis in ionic liquids allows a better control on the nanostructuration of the materials (particles size, porosity, and pore size) than simple hybridization, where an inorganic material is impregnated on a conductive carbonbased material (graphene and carbon nanotubes).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37] The ionic liquids (IL) used as (co)solvent are also able to play the key role of surfactants and/or structure directing agents allowing us to tailor the size, the shape and the agglomeration/porosity of the synthesized inorganic nanomaterials and hybrid nanomaterials. [38][39][40][41][42][43][44] In fact, ILs can form extended hydrogen-bond systems in the liquid state to be highly structured, which can serve as the "entropic driver" for spontaneous, well-dened, and extended ordering of nanoscale structures. Thus, synthesis in ionic liquids allows a better control on the nanostructuration of the materials (particles size, porosity, and pore size) than simple hybridization, where an inorganic material is impregnated on a conductive carbonbased material (graphene and carbon nanotubes).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, during the synthesis, the ILs can be strongly bonded to the inorganic material surface to modify material characteristics such as the solubility, stability, chemical reactivity or energy transfer properties. 36,39,[45][46][47][48][49] For instance, B. G. Choi et al synthesized a BMIMBF 4 -Co(OH) 2 hybrid electrode material and have shown by DFT calculations that ILs tethered to the Co(OH) 2 surface allow faster proton adsorption/desorption processes, which contribute to lowering the energy barrier of the pseudo-capacitive process, thus improving the electrochemical performances. 46 In this work, we report on two IL-cobalt oxyhydroxide nanohybrid materials prepared by a precipitation method.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the amounts of ionic liquids in the mixtures [46,47], thermogravimetric analysis (TGA) measurements were performed (see Figure S2 in the Supplementary Materials, for example). The TGA temperature ranges from 30 °C to 600 °C, and the total weight loss at 500 °C represents the amount of ionic liquids in the mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…Ionothermal synthesis is a perfectly adapted approach to develop nanostructured polycrystalline materials [23,24]. Ionic liquids (ILs) can be used as a solvent, capping agent, template, or even as reactants for the synthesis of inorganic or hybrid nanoparticles (NPs) with controlled morphologies [25][26][27][28][29][30]. In addition to the fact that ILs allow controlling the nanoparticles morphology and aggregation, they can also functionalize nanoparticle surfaces during synthesis, and thus, modify or bring new properties [31][32][33].…”
Section: Introductionmentioning
confidence: 99%